2016
DOI: 10.2147/tcrm.s112972
|View full text |Cite
|
Sign up to set email alerts
|

Changes in oxidative stress from tracheal aspirates sampled during chest physical therapy in hospitalized intubated infant patients with pneumonia and secretion retention

Abstract: ObjectiveThis study aimed to show the changes in oxidative stress and clinical condition from either chest physical therapy (CPT) or CPT with aerosol treatment in infant patients with pneumonia.MethodsFrom 52 intubated patients, three groups were composed: groups A, B, and C comprising 21 patients aged 5.3±0.6 months (CPT program), 20 patients aged 5.6±0.7 months (aerosol treatment before CPT program), and eleven patients aged 5.0±0.35 months (control), respectively. CPT was composed of manual percussion and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
4
4
0
Order By: Relevance
“…We found that TT and NT levels were significantly lower in both pediatric and adult COVID‐19 cases with severe disease course in the present study. Our findings supported the potential utility of using thiol levels as a predictor of COVID‐19 severity, and the higher thiol levels observed in mild or moderate cases may serve as an indirect indicator of the improved antioxidant status in lung tissues due to better control of the proinflammatory processes in the lungs 24 . Additionally, our data showed that the TT and NT levels were lower in adults than in children with COVID‐19, and these levels appeared to be good predictors of COVID‐19 diagnosis, particularly among adults.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We found that TT and NT levels were significantly lower in both pediatric and adult COVID‐19 cases with severe disease course in the present study. Our findings supported the potential utility of using thiol levels as a predictor of COVID‐19 severity, and the higher thiol levels observed in mild or moderate cases may serve as an indirect indicator of the improved antioxidant status in lung tissues due to better control of the proinflammatory processes in the lungs 24 . Additionally, our data showed that the TT and NT levels were lower in adults than in children with COVID‐19, and these levels appeared to be good predictors of COVID‐19 diagnosis, particularly among adults.…”
Section: Discussionsupporting
confidence: 78%
“…Our findings supported the potential utility of using thiol levels as a predictor of COVID‐19 severity, and the higher thiol levels observed in mild or moderate cases may serve as an indirect indicator of the improved antioxidant status in lung tissues due to better control of the proinflammatory processes in the lungs. 24 Additionally, our data showed that the TT and NT levels were lower in adults than in children with COVID‐19, and these levels appeared to be good predictors of COVID‐19 diagnosis, particularly among adults. The better thiol/DD balance observed in children might indicate they might are better protected from the harmful effects of oxidative stress than adults.…”
Section: Discussionmentioning
confidence: 59%
“…24 Many studies have investigated thiol status in adults and children with different diseases including acute tonsillopharyngitis, meningism, meningitis, acute appendicitis, Crimean-Congo hemorrhagic fever (CCHF), and brucellosis, 21,[25][26][27][28] but few studies have examined thiol status in patients with CAP. 29,30 Consistent with our results, previous studies have found that patients had lower TT and NT levels compared with control groups. 21,25,26,28 Moreover, Aycicek et al and Oncel et al reported the same results in children as in our study.…”
Section: Discussionsupporting
confidence: 92%
“…27,28 However, our finding that outpatients had higher thiol levels supports the potential utility of thiol level as a predictor of the need for hospitalization in patients with CAP, because the higher levels in outpatients may indirectly indicate improved antioxidant status in the lung tissue due to better control of the proinflammatory processes in the lungs. 30 In one of our previous studies focused on the oxidant status of patients with CCHF, we reported that high TT may be protective against the development of CCHF infection. In other words, similar to the literature, the progression of inflammatory processes cannot be inhibited without adequate thiol levels, as in the inpatients of our study.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, Aycicek et al and Oncel et al reported the same results in children as in our study 24,25 . However, our finding that outpatients had higher thiol levels supported the potential utility of thiol level as a predictor of CAP severity, because the higher level in outpatients may be an indirect indicator of improved antioxidant status in the lung tissue due to better control of the proinflammatory processes in the lungs 27 . In one of our previous studies focused on the oxidant status of patients with CCHF, Oncel et al reported that high TT may be protective against the development of CCHF infection.…”
Section: Discussionsupporting
confidence: 50%